2014
DOI: 10.1111/1750-3841.12588
|View full text |Cite
|
Sign up to set email alerts
|

Color and Volatile Analysis of Peanuts Roasted Using Oven and Microwave Technologies

Abstract: Peanuts can be roasted to equivalent colors and have similar volatile levels by different roasting methods. Oven and microwave roasting technologies produced the same roasted peanut color and had similar volatile trends as roasting time increased. Combination roasting also produced ideal color and similar volatile levels indicating that microwave technology could be further explored as a peanut roasting technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 57 publications
(90 reference statements)
0
19
0
Order By: Relevance
“…Roasting at a higher temperature and for a longer duration resulted in a significant ( P ≤ 0.05) decrease in the lightness ( L * value) of the sample; the redness ( a * value) and yellowness ( b * value) of the sample, however, significantly ( P ≤ 0.05) increased. This is the result of Maillard reaction and caramelization, which are enhanced at increased temperature and time (Kim and others ; Agila and Barringer ; Smith and Barringer ). An increase in the total color difference (Δ E * value) of rice roasted by hot air was higher than that roasted by superheated steam, especially at 170 °C (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Roasting at a higher temperature and for a longer duration resulted in a significant ( P ≤ 0.05) decrease in the lightness ( L * value) of the sample; the redness ( a * value) and yellowness ( b * value) of the sample, however, significantly ( P ≤ 0.05) increased. This is the result of Maillard reaction and caramelization, which are enhanced at increased temperature and time (Kim and others ; Agila and Barringer ; Smith and Barringer ). An increase in the total color difference (Δ E * value) of rice roasted by hot air was higher than that roasted by superheated steam, especially at 170 °C (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of oven, microwave or combined oven–microwave roasting on peanut volatiles and colour, were reported by Smith and Barringer . In general it was found that volatile levels increased with an increase in roasting time or temperature.…”
Section: Current Applications Of Sift‐ms In Food Aroma Analysismentioning
confidence: 72%
“…Barringer. 69 In general it was found that volatile levels increased with an increase in roasting time or temperature. Both oven and microwave roasting technologies produced similar volatile trends and peanut colour with increasing roasting time, and the results of combination roasting also showed promise for further investigations into microwave technology for peanut roasting.…”
Section: Nuts Seeds and Grainsmentioning
confidence: 98%
See 1 more Smart Citation
“…The CIE L * value is an indicator of the degree of roasting of peanuts. An L * value greater than 61 is the standard that indicates an under‐roasted or raw peanut . All treatments resulted in peanuts with L * values greater than 61 (Table ).…”
Section: Resultsmentioning
confidence: 99%